THE INFLUENCE OF USING EDUCATIONAL MEDIA WITH ANIMATED VIDEOS ON THE LEVEL OF KNOWLEDGE OF TEENAGE GIRLS ABOUT TEENAGE PREGNANCY - Bunga Zulfa Salsabila; Nana, Dwi Ratna; Siti Munawaroh (Journal for Quality in Women's Health, 2025)
Teenage pregnancy is a major public health issue in low-and middle-income countries. This issue has a significant impact on health of young mothers, infant development, and society as a whole. Teenage pregnancy can affect the physical, psychological, economic, and social health of women in the long term, so it requires serious attention in healthcare system. To determine the effect of using educational media with animated videos on the level of knowledge of teenage girls about teenage pregnancy at SMK Kesatuan, West Jakarta. This study used a quantitative analytical method with a quasi-experimental design and a pre-test post-test with one group